Smarthealth Sleman: Aplikasi Prediksi Penyebaran Tuberkulosis Dengan Kejadian Anemia Berbasis Artificial Intelligence - Anwarudin Anwarudin; Desto Arisandi; Hieronymus Rayi Prasetya (Riviera Publishing, 2025)
The need to find TB cases early and be able to provide accurate and reliable predictions of TB spread requires applications to support government programs in TB prevention and control. Through the development of the